Considerations on the low-pressure exhaust gas recirculation system control in turbocharged diesel engines. (February 2014) - Luján, José M; Guardiola, Carlos; Pla, Benjamím; Cabrera, Pedro
Although high-pressure exhaust gas recirculation has been commonly used in turbocharged diesel engines for controlling the NOx formation, recent advances in after-treatment and material technology make possible using a low-pressure architecture, which recirculates the exhaust gas upstream the compressor. This brief article presents a basic study of control aspect related to the low-pressure architecture, emphasising the similarities and differences with the high-pressure system. Data from experimental tests with both configurations and from a one-dimensional wave action model simulations are combined for the analysis of the input–output paring, linearity and the transient performance of both systems.